Benarkah Kita Murji’ah? Catatan atas Artikel Prof. Dr. Fauzan Saleh - Amal Fathullah Zarkasyi (Universitas Darussalam Gontor, 2014)
This is a special note on the article written by Fauzan Saleh entitled Kita Masih Murji’ah: Mencari Akar Teologi Pemahaman Umat Islam Indonesia published in Tsaqafah Volume 7, No. 2, October 2009. The author notes that the article could plunge Muslims to the wrong conception. Fauzan begins his article on Caliph Uthman’s nepotism when designating Amr bin Ash as governor of Egypt, Mua’wiyah as governor of Sham and Sa’ad bin Abi Waqas as governor of Iraq and Persia. Further this article notes concerning the definition of Ahl al- Sunnah wa al-Jama’ah. In addition, the author sees Fauzan does not fully understand this concept. Thus, because he classified both Maturidist and Asy’arist only into this group, without explaining their true set of belief. Actually the truth about Ahl al-Sunnah wa al-Jama’ah is the groups who have unanimity in beliefs, traditions and the status of Prophet Muhammad (Peace be upon him) and the the very righteous people among Muslims in Islam. They are the prophet’s companions and Tabi’in (followers), and the schoolars who followed their guidance, and their way in terms of faith, words, and deeds until the Day of Judgment. From this point of view, the criticism persists about the actors a great sin whereby this article parsed differences between Ahlusunah and Murji’ah. According to the author, Fauzan has been on failure when he drew a hasty conclusion at the similarity belief of Murji’ah and Ahlusunah, whereas Ahlusunah’s creed is just a continuation of Murji’ah’s. As clearly written in Fauzan’s conclusions of the article, despite Murji’ah creed is no longer known at this time, but this concept still remains sustainable in Islamic theology.